Sleep Quality and Associated Factors Among Firefighters in Bangkok, Thailand: A Cross-sectional Study - Nunnapat Piyachaiseth; Pornchai Sithisarankul; Jate Ratanachina (Korean Society for Preventive Medicine, 2024)
Objectives: Professional firefighters face various health hazards and are required to maintain both physical and mental fitness to effectively mitigate crises and respond to emergencies. Moreover, the long working hours and shift work of this profession impact sleep quality. This study investigated the quality of sleep and its associated factors among firefighters in Bangkok, Thailand. Methods: This was a cross-sectional study of firefighters affiliated with the Bangkok Fire and Rescue Department, Bangkok Metropolitan Administration, Thailand between January 2023 and March 2023. A cluster random sampling technique was utilized to distribute 600 questionnaires to firefighters in 15 fire stations. The questionnaire addressed demographic, work-related, and environmental factors. Sleep quality was assessed using the Thai version of the Pittsburgh Sleep Quality Index (PSQI). Data analysis involved both descriptive and inferential statistics. Bivariate and multiple logistic regressions were performed. Results: The response rate was 78.7% (n=472), and 44.1% of the firefighters reported poor sleep quality (PSQI score >5). Sleep quality was statistically associated with conflicting family relationships (odds ratio [OR], 1.8; 95% confidence interval [CI], 1.1 to 2.9), additional part-time jobs (daytime, OR, 2.4; 95% CI, 1.3 to 4.4; or nighttime, OR, 4.3; 95% CI, 1.1 to 16.7), noisy sleeping areas (OR, 1.7; 95% CI, 1.1 to 2.8), and the availability of adequate bedding (OR, 3.0; 95% CI, 1.8 to 4.9). Conclusions: Poor sleep quality among firefighters was associated with various personal, work-related, and environmental factors. Organizations should promote policies that improve sleep quality through good sleep hygiene practices and facilities.